Could inducible protein-10 and heparin-binding hemagglutinin improve the detection of Mycobacterium tuberculosis-infected subjects in a country with low incidence of tuberculosis ?. Issue 8 (August 2015) - Molicotti, Paola; Bua, Alessandra; Cubeddu, Marina; Ruggeri, Melania; Mura, Maria Stella; Pirina, Pietro; Zanetti, Stefania
Abstract: Background: This study aimed to evaluate inducible protein-10 (IP-10) as a biomarker besides interferon-gamma (IFN-γ) to improve the identification of active tuberculosis (TB) and latent tubercular infection (LTBI) in a country with a low incidence of TB. Methods: Whole blood from Mycobacterium tuberculosis -infected subjects was stimulated with region-of-difference-1 (RD1)-specific peptides and with heparin-binding hemagglutinin (HBHA) to determine the release of IP-10 and IFN-γ. Results: No statistically significant difference was observed between positive rates of IP-10 and IFN-γ after RD1-specific peptide stimulation in the TB and LTBI groups; a different response was detected in QuantiFERON TB-gold test-negative (QFT–) subjects. A significantly different proportion of positive responses was observed between IP-10 and IFN-γ following HBHA stimulation in the TB group and in the QFT– group but not in the LTBI group. Conclusions: The IP-10 test seemed to identify false-negative QFT results in some subjects with a positive IFN-γ/IP-10/HBHA pattern.